Spinal anesthesia in children: most pediatric urologists are not on board. Issue 3 (May 2019) - Rehfuss, A.; Bogaert, G.; Kogan, B.A.
Summary: Objective: In 2016, the Food and Drug Administration issued a warning on general anesthetic medications used for lengthy procedures (>3 h) in children younger than 3 years. Spinal anesthesia can be a safe alternative to general anesthesia for many pediatric urology procedures. It can shorten total operating room (OR) time, provide excellent pain control, and allow parents to reunite with their child immediately after surgery. However, use of spinal anesthesia can also directly affect the operating surgeon (awake patient, time constraints of spinal, and prolonged preoperative time). Members of the Societies for Pediatric Urology (SPU) and European Society of Pediatric Urology (ESPU) were surveyed to get their opinions on the use of spinal anesthesia for routine pediatric urology procedures. It was hypothesized that half of pediatric urologists would favor spinal anesthesia and that SPU members would be more likely to favor spinal anesthesia than their European colleagues. Materials and methods: A short survey with five clinical scenarios was created. Scenarios assessed physicians' recommendations regarding timing and the type of anesthesia (general or spinal) for common pediatric urology procedures: undescended testicle, inguinal hernia, hypospadias, phimosis, and phimosis with penoscrotal webbing. Surveys were emailed to members of the SPU and ESPU. Responses and demographic information were collected and analyzed. Results: The survey was completed by 113 SPU members (46% response rate for members who opened the invitation) and 109 ESPU members. For all clinical scenarios, < 20% of pediatric urologists from the SPU and <25% from the ESPU favor doing any procedure with spinal anesthesia. The majority of respondents practice in children's hospitals with pediatric anesthesiologists, but roughly half of the responders (54% SPU and 43% ESPU) do not think their anesthesia colleagues would be comfortable performing spinal anesthesia. Furthermore, only 51% of SPU and 36% of ESPU members discuss the possible neurodevelopmental side-effects of anesthesia with parents; similarly, less than half of all respondents think their anesthesia colleagues address these potential side-effects when obtaining consent. The only significant difference between SPU and ESPU responses was that ESPU members tended to delay penile surgery more than SPU respondents. Conclusion: Whether general anesthesia has any effect on the developing brain of children undergoing routine pediatric urology procedures is unclear. Yet, few pediatric urologists, independent of their region of practice, prefer spinal to general anesthesia. Collaboration in the OR is the key to success, and it is important that pediatric urologists and pediatric anesthesiologists work together to balance the benefits and risks of general and spinal anesthesia.Would you rather do this operation with spinal anesthesia only (no general anesthesia) in a healthy 5-month-old male? Clinical scenario Yes No Palpable unilateral undescended testicle (UDT) SPU, 15% ESPU, 18% SPU, 85% ESPU, 82% Unilateral inguinal hernia with bowel in it SPU, 19% ESPU, 25% SPU, 81% ESPU, 75% Distal shaft hypospadias SPU, 10% ESPU, 20% SPU, 90% ESPU, 80% Phimosis with penoscrotal webbing SPU, 19% ESPU, 23% SPU, 81% ESPU, 77% Phimosis, no webbing SPU, 19% ESPU, 24% SPU, 81% ESPU, 76%